Direct catalytic enantio- and diastereoselective Mannich reaction of isocyanoacetates and ketimines. - Ortín, I; Dixon, D (Wiley, 2014)
A catalytic asymmetric synthesis of imidazolines with a fully substituted β-carbon atom by a Mannich-type addition/cyclization reaction of isocyanoacetate pronucleophiles and N-diphenylphosphinoyl ketimines has been developed. When a combination of a cinchona-derived aminophosphine precatalyst and silver oxide was employed as a binary catalyst system, good reactivity, high diastereoselectivities (up to 99:1 d.r.), and excellent enantioselectivities (up to 99% ee) were obtained for a range of substrates.